Recognition of Customary Law in The Perspective of Indonesian Criminal Law - Kadir, Syukron Abdul; Chrisjanto, Edy; Suyikati, Suyikati (UNISKA LAW REVIEW, 2026)
This study examines the recognition of customary law in the perspective of Indonesian criminal law as a response to the pluralistic character of society and the dynamics of National Legal Reform. Since colonial times, customary law has been understood as living law, that is, norms that are alive and have social binding power even though they are not codified. In recent developments, the recognition of the law that lives in society gained legitimacy in the new criminal code, but still caused tension with the principle of legality through the principle of nullum crimen sine lege. The research method used is normative legal research with legislation and conceptual approach. As a result of the discussion, the existence of customary law in Indonesian criminal law offers restorative potential and socio-cultural values that enrich the criminal system, especially through the rapprochement of perpetrators, victims, and the community. However, unwritten customary norms pose challenges to legal certainty, principles of legality, and Human Rights. The integration of customary law into the new penal code allowed for a restorative approach that was responsive to local needs, particularly minor crimes. In order to remain in line with the principles of the modern rule of law, integration must be carried out in a measurable manner through clear regulation, institutional supervision, normative harmonization, and multidisciplinary involvement, thus preventing inconsistency, discrimination, or legal irregularities. Keywords: customary law, principle of legality, Restorative Justice..